Synthesis and Characterization of Magnesium Acetate Doped MAPbI3 Perovskite Solar Cells with Carbon Electrodes - Deris Afdal Yusra; Nandang Mufti; Eny Latifah (Universitas Negeri Malang, 2021)
The organometal perovskite trihalide (MAPbI3) based solar cell has attracted the attention of many researchers because it has the potential to be a third-generation solar cell that has high efficiency, flexibility and transparency. However, this perovskite solar cell is sensitive to the environment and less stable. In this study, a performance study of perovskite solar cells with the addition of magnesium acetate was carried out in the MAPbI3 synthesis process and the use of carbon electrodes. In general, the perovskite solar cell arrangement in this study consisted of ITO/TiO2 mp/MAPbI3/carbon paste. Mesoporous TiO2 (mp) coating was carried out using the screen printing method, while MAPbI3 coating was carried out with a two-stage spin coating with the addition of magnesium acetate after PbI2 coating in the first stage. The samples obtained were then characterized using an X-Ray Diffractometer (XRD). Analysis of the performance of solar cells was carried out by measuring I-V and photoresponses using a solar simulator. XRD results show that MAPbI3 film has been formed even though there is still impurity of PbI2. The resulting solar cell performance has a value of Voc equals 3.45 V and Jsc equals 0.04 with an efficiency of around 0.09 per cent. In the measurement of the response photo, the increase in time value was 7.29 s and the decay time was 34.38 s. The low-efficiency value is probably due to the absence of a layer of hole transfer materials (HTM) and the presence of PbI2 impurities. However, the stability of the photoresponse pattern against time has shown quite good results even though the response is increased or the decay is slow.DOI: 10.17977/um024v6i22021p040